Perjalanan Songket: Transformasi Menghidupkan UMKM di Kota Palembang - R.A Rodia Fitri Indriani; Marsinah Marsinah; Dwi Hanadya; Nyayu Ully Auliana; M. Bambang Purwanto (Universitas 45 Surabaya, 2024)
Songket, as one of Indonesia's textile cultural heritage, has a long history that reflects the richness of tradition and outstanding craftsmanship. However, in recent decades, songket has faced challenges that threaten its survival, including fashion changes, lack of artisan regeneration, and competition with modern textile products. This article explores the journey of songket from its heyday in the past to the revitalization efforts made to restore that glory in the modern era. Through a qualitative approach, this study explores strategies applied by various stakeholders, including craftsmen, designers, government, and communities, to maintain and promote songket as a relevant cultural product with high economic value. Case studies from various songket-producing regions in Indonesia show that design innovation, education, and cross-sector collaboration play an important role in this process. The results of this study provide insight into how reviving cultural heritage can be a source of pride and economic sustainability for local communities. In conclusion, songket's journey from heritage dreams to real glory is an inspiring example of how traditional cultural richness can be integrated into contemporary contexts to create sustainable benefits.